Practical guidance for dosing and switching from paliperidone palmitate 1 monthly to 3 monthly formulation in schizophrenia. (2nd November 2015) - Gopal, Srihari; Vermeulen, An; Nandy, Partha; Ravenstijn, Paulien; Nuamah, Isaac; Buron Vidal, José Antonio; Berwaerts, Joris; Savitz, Adam; Hough, David; Samtani, Mahesh N.
Abstract: Objective: This commentary summarizes recommended dosing strategies for a recently developed 3 monthly long-acting injectable1 (LAI) formulation of paliperidone palmitate (PP3M) for the treatment of schizophrenia in adults. Methods: Recommendations for different dosing scenarios are based on the pharmacokinetic, efficacy and safety outcomes from phase 1 and phase 3 studies, population pharmacokinetic models, and model based simulations. Results: Switching to PP3M treatment is recommended only in patients previously treated with once monthly paliperidone palmitate LAI (PP1M) for at least 4 months. The first injection of PP3M (175 to 525 mg equivalent [eq.]) should be given at the time of next scheduled injection of PP1M as a 3.5-fold multiple of the last PP1M dose (50–150 mg eq.), with a dosing window of ±1 week. Following that first injection of PP3M, once-every-three-months maintenance injections with PP3M are recommended, with a dosing window of ±2 weeks. The doses of PP3M can be administered in either deltoid (≥90 kg: 1.5 inch 22 G needle; <90 kg: 1.0 inch 22 G needle) or gluteal muscles (1.5 inch 22 G needle regardless of weight). In patients with mild renal impairment (creatinine clearance: 50–80 mL/min), a 25% dose reduction in PP1M and subsequent switching to a corresponding 3.5-dose multiple of PP3M (but not exceeding 350 mg eq.) is recommended. Appropriate dosing is recommended in elderly patients with diminished renal function not exceeding mild renal impairment. Similarly to PP1M, PP3M is not recommended in patients with moderate/severe renal impairment. Like PP1M, no dosage adjustment is required in patients with mild or moderate hepatic impairment or elderly patients with normal renal function. Conclusions: These data provide clinical guidelines for the optimum use of PP3M in patients with schizophrenia previously treated with PP1M for at least 4 months. Registration: ClinicalTrials.gov identifier: NCT01559272 and NCT01529515.